1(3)‐Formyl‐β‐carbolines: Potential Aldo‐X Precursors for the Synthesis of β‐Carboline‐Based Molecular Architectures. Issue 1 (20th November 2017) - Devi, Nisha; Kumar, Sunit; Pandey, Satyendra Kumar; Singh, Virender
Abstract: β‐Carboline, a privileged scaffold in the alkaloid family, has a broad spectrum of medicinal properties and is found in several commercial drugs, such as tadalafil, cipargamin, and abecarnil. Owing to the immense pharmacological importance of β‐carboline derivatives, their synthesis has been one of the frontier areas of research in recent years. In this context, 1(3)‐formyl‐9 H ‐β‐carbolines are promising "aldo‐X" bifunctional building blocks (AXB3s) that offer alternate avenues for the diversity‐oriented synthesis of β‐carboline derivatives. This Focus Review is an assimilation of recent literature (2011–2017) pertaining to the synthesis and applications of 1(3)‐formyl‐β‐carbolines for the construction of β‐carboline‐tethered and ‐fused molecular architectures. In addition, the medicinal potential of β‐carboline derivatives has been highlighted. Abstract : Generation X : The various methods for the diversity‐oriented synthesis of β‐carboline derivatives through an exploration of Kumujian C and its analogues are highlighted and summarized, which provide an excellent alternative to the classical Pictet–Spengler approach.